2022
DOI: 10.1002/hsr2.931
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline use and adverse pregnancy or neonatal outcomes: A descriptive study using the United States Food and Drug Administration Adverse Event Reporting System database

Abstract: Background and Aims Doxycycline is recommended for use in rickettsial diseases. The available evidence regarding its safety for rickettsial infection in pregnancy is limited. Our study aimed to describe the adverse events of doxycycline when used during pregnancy for any indication, in terms of adverse maternal and/or neonatal outcomes, using the United States Food and Drug Administration Adverse Event Reporting System (FAERS). Methods We used the OpenVigil software for extracting the safety reports from the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…However, the database may be biased by a number of confounding factors; identification of drugs that may cause SVT in the OpenVigil database does not indicate a drug–adverse event causal association. 43 , 44 Additionally, in our study, drugs found in the OpenVigil database that could potentially cause SVT were further assessed using the Hangzhou Yiyao Rational Use System, SIDER database, and several research literature databases. However, the aforementioned sources have a certain lag time, such as lengthy update time of drug specifications.…”
Section: Discussionmentioning
confidence: 99%
“…However, the database may be biased by a number of confounding factors; identification of drugs that may cause SVT in the OpenVigil database does not indicate a drug–adverse event causal association. 43 , 44 Additionally, in our study, drugs found in the OpenVigil database that could potentially cause SVT were further assessed using the Hangzhou Yiyao Rational Use System, SIDER database, and several research literature databases. However, the aforementioned sources have a certain lag time, such as lengthy update time of drug specifications.…”
Section: Discussionmentioning
confidence: 99%
“…Doxycycline is effective for the treatment of LAM [ 56 ], but the use of doxycycline during pregnancy has historically been discouraged due to potential adverse effects on the fetal teeth during 16 weeks postconception. Although a study assessed doxycycline use during pregnancy [ 57 ], the data are insufficient to state that there is no risk. So clinical trial guidelines do not suggest the use of doxycycline as a treatment for LAM because there are no beneficial effects in LAM patients who already have lung function impairment.…”
Section: Treatment During Pregnancymentioning
confidence: 99%
“…Most pregnant women with murine typhus have favorable outcomes, but poor neonatal outcomes from those with suboptimal treatment have been reported [163,164]. Doxycycline does not seem to be associated with the severe adverse events in pregnant women that have been reported with older tetracyclines [165,166].…”
Section: Treatment and Preventionmentioning
confidence: 99%